Forward Surgery On Operation Telic – Iraq 2003. Issue 3 (1st September 2005) - Parker, P J; Adams, S A; Williams, D; Shepherd, A
Abstract : Two Air Assault Surgical Groups (AASGs) from 16 Close Support Medical Regiment deployed to Kuwait on Operation Telic in February 2003. Each AASG was comprised of a four-table resuscitation facility, a two table FST and a twin-bedded ITU facility. An A+E Consultant and nurse, an experienced radiographer and laboratory technician with two further RGNs and CMTs provided resuscitation support. Each FST had an orthopaedic and a general surgeon, two anaesthetists and eight operating department practitioners. Further equipment consisted of a Polymobil 111 X-ray unit, a Sonosite 180 ultrasound scanner and an ISTAT gas, haematocrit and electrolyte analyser. 100 units of mixed blood were carried by each AASG. Fifty-one surgical procedures were performed on thirty one patients. Twenty one of these patients were Iraqi prisoners of war or civilians. Seventeen wound debridements, five amputations, five laparotomies, four insertions of Denham pins with Thomas splintage for femoral fracture, three external fixations and one axillary artery repair formed the basis of the major cases undertaken. The first field use of activated factor VII by the British Army was successful in the resuscitation of a patient with exsanguinating haemorrhage after an open-book (APC-III) pelvic fracture and a ruptured intrapelvic haematoma. The other cases included eleven manipulations under anaesthetic/application of plaster and four finger terminalisations. Forward military surgery has a continued role to play on the modern fast moving battlefield. 16 Close Support Medical Regiment normally supports 16 Air Assault Brigade with its remit for expeditionary operations and SF support. Its experience on Op Telic should influence planning for future deployment.